2022
DOI: 10.3233/ves-190755
|View full text |Cite
|
Sign up to set email alerts
|

The clinical characteristics and anatomical variations in patients with intractable unilateral Meniere’s disease with and without migraine

Abstract: BACKGROUND: Migraine is more common in Meniere’s disease patients, who have some certain anatomical variations. But there are limited studies focusing on the anatomical variations in patients with Meniere’s disease and migraine. OBJECTIVE: To explore the clinical and anatomical features in Meniere’s disease patients with and without migraine, determining whether the coexistence of migraine can be used as a basis for clinical subtyping of Meniere’s disease. METHODS: Ninety-five Meniere’s disease patients and ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…13 There was a greater rate of migraine in female patients with MD, clinical manifestations of frequent vertigo attacks, better hearing levels, and specific anatomical features. 13 The large study population could potentiate the reciprocal association between MD and migraine in subgroups of this study. Although a significant association between MD and migraine was observed in all subgroups, the middle-aged, male, and comorbid conditions of hyperglycosemia and hypercholesterolemia subgroups showed a stronger association between the 2 diseases in this study.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…13 There was a greater rate of migraine in female patients with MD, clinical manifestations of frequent vertigo attacks, better hearing levels, and specific anatomical features. 13 The large study population could potentiate the reciprocal association between MD and migraine in subgroups of this study. Although a significant association between MD and migraine was observed in all subgroups, the middle-aged, male, and comorbid conditions of hyperglycosemia and hypercholesterolemia subgroups showed a stronger association between the 2 diseases in this study.…”
Section: Discussionmentioning
confidence: 94%
“…The bidirectional associations between MD and migraine were valid in all subgroups. In contrast, a cross-sectional study examined the specific features of patients with MD combined with migraine . There was a greater rate of migraine in female patients with MD, clinical manifestations of frequent vertigo attacks, better hearing levels, and specific anatomical features .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The following five distinctive clinical subtypes have been identified by the Ménière's Disease Consortium (61): Type 1 included patients without a familial history of MD, migraine, or autoimmune comorbidity; Type 2 had delayed MD characterized by SNHL which antedated the vertigo episodes; Type 3 included all familial cases of MD; Type 4 was associated with migraine with or without aura, and Type 5 was defined by a concurrent autoimmune disorder (61). Recently, Diao et al found that some radiological variables differed between patients with MD with and without migraine, including the poorer mastoid pneumatization and the shorter distance between the sigmoid sinus and posterior wall of the external acoustic canal (62). Then, it is reasonable to suppose that the anatomical variations may play inconsistent roles in different subtypes of unilateral MD.…”
Section: Differential Diagnostic Value Of Radiological Variations Bet...mentioning
confidence: 99%